Impact of first-line chemoimmunotherapy with or without radiotherapy on the prognosis of patients with locally advanced or metastatic esophageal squamous cell carcinoma: a multicenter, real-world, retrospective cohort study from China (NCT06478355) - Liu, Xinyi; Wen, Jingyuan; Zhang, Yaowen; Wang, Chenyu; Liu, Yatian; Qian, Pudong; Cao, Jianzhong; Hou, Qing; Xu, Yuanji; Lin, Zhongmei; Ye, Xianghua; Hou, Min; et al. (Frontiers in Immunology, 2025)
BackgroundChemotherapy combined with immunotherapy has already become the standard first-line treatment for advanced or metastatic esophageal squamous cell carcinoma (ESCC), whereas there are no satisfying overall survival (OS) and progression-free survival (PFS). This research aims to evaluate whether first-line chemoimmunotherapy combined with radiotherapy (RT) improves outcomes and safety in patients who suffer from locally advanced and metastatic ESCC.MethodsA total of 664 patients who suffer from locally advanced or metastatic ESCC going through first-line chemoimmunotherapy with or without radiotherapy at China’s 11 large cancer centers from Jan. 2019 to Dec. 2022 were retrospectively explored. Each patient received first-line chemoimmunotherapy, and the specific program was determined by the investigator. Regarding the radiotherapy group, each patient went through radiotherapy with a dose of ≥30 Gy to the primary lesion. Through utilizing the log-rank test, Kaplan-Meier survival curves were set up and then compared. The research carried out prognostic analysis by harnessing the univariate and multivariate Cox proportional hazards regression models. To find out patient characteristics and treatment patterns related to treatment responses, we also conducted subgroup analyses. The possible biases were minimized through performing the propensity score matching (PSM). This trial has been registered at ClinicalTrials.gov (NCT06478355, Registration date: June 22, 2024).ResultsThe research enrolled 664 patients in total, of which 438 received radiation therapy (ICRT group) and 226 received immunotherapy combined with chemotherapy alone (ICT group). In the overall cohort, the median follow-up was 37.0 months (IQR: 35.7-38.3). Compared to those in the ICT group, the median OS and median PFS in the ICRT group were significantly longer (mOS,33 versus 20 months, P < 0.001;mPFS, 15 versus 12 months, P < 0.001). To reduce the effect of bias, the two groups went through a 1:1 PSM analysis. The study assessed 334 patients, in which a total of 167 patients were evaluated in every subgroup. The analysis demonstrated that adding radiotherapy significantly improved the median OS (mOS, 34 versus 20 months, P=0.015) and PFS (mPFS, 16 versus 12 months, P=0.008), consistent with the pre-match results. According to the multivariate COX regression analysis, radiotherapy served as one of the independent prognostic factors that impact OS (HR=0.67,95%CI:0.50-0.89, P=0.006) and PFS (HR=0.68,95%CI:0.53-0.89, P=0.004). There were greatly prolonged both OS (HR=0.58,95%CI:0.41-0.81, P=0.002) and PFS(HR=0.61,95%CI:0.44-0.82, P=0.001) after radiotherapy within patients that just had regional lymph node metastasis. There was no benefit in OS(P=0.780) or PFS(P=0.880) within patients that had distant organ metastases. In addition, concerning patients not going through immune maintenance therapy (number of immune cycles>6), radiotherapy significantly reduced not only mortality (HR=0.66,95%CI:0.49-0.90, P=0.009) but also recurrence (HR=0.72,95%CI:0.54-0.97, P=0.028). In terms of security, ICRT group esophagitis (22.8% versus 3.6%; P<0.001), esophageal fistula (5.4% versus 0.0%; P=0.003), and pneumonia (10.8% versus 3.0%;P=0.008) all exhibited a higher incidence. Grade 3–4 pneumonia incidence was not enhanced by radiotherapy (1.8% versus 0.6%; P=0.623).ConclusionAccording to the research, adding radiotherapy into systemic chemotherapy integrated with immune checkpoint inhibitors significantly improves the prognosis of patients in China who suffer from locally advanced or metastatic esophageal squamous cell carcinoma. There is safe combined treatment, and the treatment-related adverse effects are manageable. However, large randomized controlled trials need to be carried out to further confirm those results.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT06478355, identifier NCT06478355.